The initial reasons for the revocation of a banking license of a credit institution in the context of constitutional legal proceedings - Kurakin, Aleksei Valentinovich; Karpukhin, Dmitrii Vyacheslavovich (Полицейская и следственная деятельность, 2020)
Measures of administrative coercion have become widely used in the financial segment of economic relations. The revocation of a banking license of a credit institution is one of the most popular ones. The legal mechanism of this measure of administrative coercion has been in force for three years, but its analysis in the context of application to particular credit institutions reveals a range of fundamental problems connected with the clarification of the character, the role and the place of this measure within the system of administrative coercion. The authors analyze the problem of revocation of a banking license of a credit institution as it is described in the decisions of the Constitutional Court to find the key to the understanding the solution to these problems. The academic novelty of the research consists in the analysis of legal problems of using the measures of administration coercion in the banking system. The authors pay attention to the various functions of measures of administrative coercion in the banking system, and focus on such aspect as the revocation of a banking license of a credit institution. This measure is a form of administrative coercion combining the elements of prevention, constraint, and punishment of a credit institution. The authors note that the revocation of a banking license is one of the most serious measures of administrative coercion, and it is important to observe the constitutional principles of using it.